IDENTITAS KAUM SAMIN PASCA KOLONIA PERGULATAN NEGARA, AGAMA, DAN ADAT DALAM PRO-KONTRA PEMBANGUNAN PABRIK SEMEN DI SUKOLILO, PATI, JAWA TENGAH - Munawir Aziz (Jurnal Kawistara, 2012)
Memmories of colonization have created an ethos of daily struggle among the followers of Saminism. Encounters with colonialism in the early 20 th century impacted Samins’ character, ethos, and worldview, as demonstrated through their way of dealing with the Indonesian government, corporations, and other communities. This impact is evident in the case of the establishment of the Semen Gresik factory in Sukolilo, Pati, Central Java. The project plan of establishing a cement factory and exploration of Kendeng Mountain at Sukolilo created con ict among the people of Pati. The people were divided into two groups. The rst supported the exploration and the second resisted. Samins, however, resisted it and stood against it for their environment. This article examines the Samins actions when dealing with outside powers, in this case the State and the cement corporation. It also studies how the Samins constructed their post-colonial worldview and identity in response to the state, religion, and capitalism. Using Gayatri sivak’s theory of “subalternity”, this article explains identity politics of the post-colonial Samin Movement.